Analisis kinerja keuangan pt. Bank mega syariah periode 2019 – 2023 - febriyansyah, dimas almadani (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the financial performance of PT. Bank Mega Syariah during the period 2019-2023 with a focus on the capital adequacy ratio, operational efficiency, and profitability. The method used is a quantitative descriptive analysis method through financial ratios including the capital adequacy ratio (CAR), efficiency (BOPO), and profitability (ROA, ROE, NI), to evaluate the bank's financial health. The results of the study indicate that BMS has strong capital with a significant increase in CAR, but faces challenges in operational efficiency with an increase in the BOPO ratio. Meanwhile, BMS's profitability fluctuates, mainly influenced by external factors such as expansion costs and inflation. This study concludes that although BMS shows progress in terms of capital and profitability, operational efficiency improvements are needed to strengthen competitiveness and support sustainable growth.